EFFICACY OF HERBAL MEDICINES IN TREATMENT OF RESPIRATORY INFECTIONS - Karkinski, Dimitar; Stoshevski, Bojan; Angelovska, Irina; Poposka, Biljana; Krstikj, Olivera Nakova; Pejkovska, Sava; Manusheva, Nancy; Stefanovska, Vesna Velikj; Dokij, Dejan (Journal of Morphological Sciences; Vol 7 No 2 (2024): JMS, 2024)
Respiratory infections, especially viral ones, are the most common type of diseases that occur in humans, and the improper prescribing and abuse of antibiotic therapy is clearly described in almost all countries in the world. Herbal medicine is as old as mankind and forms the basis of modern pharmacy, so it has much to offer for patients with the common cold, viral pharyngitis, acute bronchitis and flu. The aim of this study was to investigate the efficacy of the herbal medicines Broncho Protect and Andrographis Extract, as dietary supplements, against standard medical treatment in patients with proven acute upper and/or lower respiratory tract infection. Materials and methods. The study was conducted at PHI University Clinic for Pulmonology and Allergology-Skopje as a prospective, double-blind, randomization study. 40 patients with clinical symptoms of acute upper and/or lower respiratory tract infection were included. The patients were randomized into two groups where the first group received standard therapy without restrictions plus placebo and the second group which, in addition to standard therapy, also received Bronho Protect twice a day after a meal at 15 mL and Andographis Extract at one capsule twice a day after a meal, during from 7 days. Results. The results of the patients' self-assessment of their health status indicate that there was a statistically significant improvement in both groups, but there was no difference in the final goal. The results of the assessment of the health status of the patients by the doctors indicate that in the group that received herbal medicines all the patients got better while in 2 patients of the placebo group there was no improvement. It was also found that auscultation findings, especially the finding of fine crackles, were significantly better in patients who received herbal medicines. Conclusion. Herbal medicines are effective for the treatment and prevention of respiratory infections and provide a much-needed alternative to ineffective antibiotics, whereby patients feel they are receiving beneficial therapy, thus reducing their tendency to seek antibiotics. Key words: herbal medicines, respiratory infections.